“Kids and Girls”: Parents convey a male default in child-directed speech - Rachel A. Leshin; Josie Benitez; Serena Fu; Sophia Cordeiro; Marjorie Rhodes (Proceedings of the National Academy of Sciences, 2025)
Adults tend to view men (more so than women) as default people , with numerous real-world consequences for gender equity. In the United States, the tendency to center men in concepts of people develops across middle childhood, yet the specific mechanisms that contribute to it remain unknown. Here, we investigate one subtle but potentially powerful social mechanism: the category labels that parents use to describe boys/men and girls/women in conversations with their children. Across two studies ( N = 822 parent–child dyads, predominantly from the United States), parents used gender-neutral labels like “kid” or “person” more often to describe boys/men than girls/women and, conversely, used gender-specific labels (e.g., “girl”) more often to describe girls/women than boys/men. These patterns emerged when parents were shown gender-stereotypical girls/women and boys/men (e.g., a girl painting her nails, a boy digging for worms); when parents viewed counterstereotypical stimuli (e.g., a boy painting his nails, a girl digging for worms), the patterns reversed. Our findings illuminate parents’ category label usage as a critical social mechanism that may undergird the development of a male default in a US cultural context, informing efforts to intervene on this process.